ANALISIS STRATEGI VISUAL PADA MAJALAH LAZY SUSAN “GORENGAN” - Muhammad Rayhan Rusyda M R; Fachmi Khadam Haeril (Universitas Mercu Buana, 2021)
Magazines still have an existence until now to provide relevant information and knowledge for them. The purpose of this research is to find out how the visual strategy used in the magazine can be a relevant information medium to read in fulfilling the fulfillment of information and knowledge. This is what makes researchers conduct research on the object of Lazy Susan's printed magazine which discusses Indonesian food (fried) that utilizes visual communication elements (layout, color, typography, pictures, illustrations) in conveying information that makes the magazine more interesting and easy to read. be read. This research is expected to be a reference to become a practical medium for making magazines on phenomena that occur in print media which are rarely in demand.